2021
DOI: 10.3390/ma14082030
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation on Dental Implant Biomaterials by Staphylococcus aureus Strains Isolated from Patients with Cystic Fibrosis

Abstract: Implants made of ceramic and metallic elements, which are used in dentistry, may either promote or hinder the colonization and adhesion of bacteria to the surface of the biomaterial to varying degrees. The increased interest in the use of dental implants, especially in patients with chronic systemic diseases such as cystic fibrosis (CF), is caused by an increase in disease complications. In this study, we evaluated the differences in the in vitro biofilm formation on the surface of biomaterials commonly used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 67 publications
1
28
0
1
Order By: Relevance
“…A study by Palka et al (2020) [26] also conclusively showed that rougher surfaces promote the susceptibility to microbial adhesion, amongst other bacterial species as well as for S. aureus and S. epidermidis. Similar findings, but for different base materials (Ti6Al4V, CoCr alloy and zirconium), have been reported by Minkiewicz-Zochniak et al, 2021 [24]. The cell count determination by means of flow cytometry was carried out to answer two questions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A study by Palka et al (2020) [26] also conclusively showed that rougher surfaces promote the susceptibility to microbial adhesion, amongst other bacterial species as well as for S. aureus and S. epidermidis. Similar findings, but for different base materials (Ti6Al4V, CoCr alloy and zirconium), have been reported by Minkiewicz-Zochniak et al, 2021 [24]. The cell count determination by means of flow cytometry was carried out to answer two questions.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, biocompatibility [19] and resistance to bacterial infections [12,[20][21][22] can be positively influenced by those newly developed materials. As mentioned above, S. aureus and S. epidermidis are especially prone to cause device-related infections, and they are used in many biofilm-related studies in the field of orthopedics [6,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Although these biomaterials were selected by us, they are also available and popular in dentistry. Our [ 34 ] laboratory studies have also shown that biofilms from S. aureus isolated from adult patients with CF can be reproducibly grown on the surface of implant biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 33 clinical strains of S. aureus identified in previous studies [ 34 ], 3 clinical strains of S. aureus were selected with their ability to form a biofilm classified as strong, moderate, weak, and non-producers. These strains were obtained from the sputum samples of patients diagnosed with CF and treated at the Department of Microbiology, National Tuberculosis and Lung Diseases Research Institute (Warsaw, Poland), Culture Collection, Department of Medical Biology, Medical University of Warsaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation